SQL Server 2008 Transact-SQL Recipes - Sack, Joseph (Apress, 2013)
The purpose of this book is to quickly provide you with the skills you need to solve problems and perform tasks using the Transact-SQL language. I wrote this book in a problem/solution format in order to establish an immediate understanding of a task and its associated Transact-SQL solution. You can use this book to look up the task you want to perform, read how to do it, and then perform the task on your own system. While writing this book, I followed a few key tenets: • Keep it brief, providing just enough information needed to get the job done. • Allow recipes and chapters to stand alone—keeping cross-references and distractions to a tolerable minimum. • Focus on features that are typically implemented entirely using Transact-SQL. For example, I cover the new Resource Governor feature because it will typically be deployed by DBAs using Transact-SQL—whereas I do not cover Policy-Based Management due to its underlying dependencies on SQL Server Agent, SQL Server Management Objects (SMO), and SQL Server Management Studio. Fortunately, most of the new SQL Server engine improvements are entirely Transact-SQL based, and therefore are included in this book. • Write recipes that help a range of skill sets, from novice to professional. I begin each chapter with basic recipes and progressively work up to more advanced topics. Regarding new SQL Server 2008 features, I have interwoven them throughout the book in the chapters where they apply. If you are just looking for a refresh on new Transact-SQL features, I specifically call them out at the beginning of each chapter in which they exist. Although a key tenet of this book is to keep things brief, you’ll notice that this book is still quite large. This is a consequence of the continually expanding SQL Server feature set; however, rest assured that the recipes contained within are still succinct and constructed in such a way as to quickly give you the answers you need to get the job done. I’ve written this book for SQL Server developers, administrators, application developers, and IT generalists who are tasked with developing databases or administering a SQL Server environment. You can read this book from start to finish or jump around to topics that interest you. You can use this book to brush up on topics before a job interview or an exam. Even for the more experienced SQL Server professionals, memory fades—and this book can help quickly refresh your memory on the usage of a command or technique. Thanks for reading!